Ritual and Boundary Distinction in a Recreational Community: A Case Study of Motorcycle Rallies and Riders - Austin, D. Mark (Qualitative Sociology Review, 2009)
Attending motorcycle rallies is an important component of social life for many touring motorcyclists. The significance of these events transcends the mere recreational experience of riding a motorcycle and spending time with other riders. This project is an examination of brand specific motorcycle rallies as a process and social world that has ritualistic features and activities that serve to bond members of the group, reinforce their identity, and distinguish members of this subculture from other motorcyclists and from the larger social world. Drawing on classical social theory and more contemporary research, a framework is established to discuss the activities and social organization of rallies. Objects from the material culture of those involved are examined as distinguishing components used to establish boundaries and confer membership. An in depth description of rally activities and interactions, enhances the understanding of these events.